Soro de queijo como substrato potencial à produção de pigmentos por Monascus ruber - Costa, Jaquelinne Pires Vital da (2017)
Research into new sources of natural pigments has grown, mainly due to the toxic effects caused by synthetic dyes used in food, pharmaceuticals, textiles and cosmetics. In this context, the microbial pigments are presented as an alternative to supply this demand. There are several microorganisms capable of producing pigments, among them the filamentous fungus, Monascus. This is capable of producing yellow, orange and red pigments, and its production depends on the conditions under which it is grown. Thus, agroindustrial wastes have emerged as a cheap and profitable option for the production of biopigments. The aim of the present study was to evaluate the use of cheese whey as a substrate for the production of pigments by Monascus ruber CCT 3802. For this purpose, we first sought to evaluate the radial growth of the fungus in solid medium under serum concentrations of cheese powder and different pH values. The results demonstrated the potential of whey as a substrate for fungus growth, since there was a significant difference between the growth rates obtained for each medium when compared to the control medium (without cheese whey). As for pH, growth rates of the fungus were higher at pH 6.0. At extreme pH values, such as pH 2.0 and 8.0, the growth of the fungus presented inhibition and the visual aspect differed, showing yellow and red coloration, respectively. This demonstrates the clear influence of pH on the production of pigments produced by M. ruber. Culture media containing glucose and cheese whey at different concentrations were studied and the results showed higher pigment production was obtained in the media containing only glucose. For this reason, the third part of the study sought to use lactose, after the enzymatic hydrolysis process, as a carbon source for the production of pigments by Monascus ruber. Culture media containing glucose, lactose and hydrolyzed lactose were incubated at 30°C in shaker for 7 days. Although it contained less than 43% of glucose, the medium containing hydrolyzed lactose presented maximum pigment production of 7.58 UA510, surpassing the culture containing glucose. The pigment produced in hydrolyzed lactose appeared lighter, but redder and more yellow than in glucose. The consumption of reducing sugars and biomass production for the culture containing lactose only were inhibited, with a decline in pigment production after 72 hours of cultivation. The results presented in this research contribute to the fact that future studies optimize the hydrolysis of lactose and, consequently, cheese whey, using it as a substrate for the production of biopigments by Monascus ruber.